PENINGKATAN KUALITAS SOSIAL KARYAWAN TAMBAK UDANG INTENSIF DAN MASYRAKAT DI DESA DADAP KECAMATAN SAMBELIA LOMBOK TIMUR - Hasani, Muhamad Shofyan; Lapanda, Agius; Sadewa, L.Wisnu Bayu; Ikhsan, Ardi; Scabra, Andre Rachmat (Universitas Mataram, 2024)
In the community service activities that we carry out together with intensive shrimp farming partners which are companies engaged in vannamei shrimp farming activities located in Dadap Village, Sambelia District, East Lombok Regency. In shrimp farming activities in intensive shrimp farming, the surrounding community is involved as employees and indirectly increases the prosperity and welfare of the community, in addition, intensive shrimp farming companies also often hold social services for local residents. The implementation of this community service was carried out from March 26, 2024 - June 23, 2024 which took place in Dadap Village, Sambelia District, East Lombok Regency, West Nusa Tenggara Province. The implementation of this activity was carried out in stages starting from the thanksgiving activity of spreading shrimp fry, distributing basic necessities to the surrounding community (Social Service), distributing takjil in Dadap Village, mutual cooperation in cleaning public roads, planting mangroves and cleaning the beach.